Factors and affect mobile telephone users to use mobile payment solution - Yan, Aw Wai; Md Nor, Khalil; Abu-Shanab, Emad A.; Sutanonpaiboon, Janejira (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Providing a convenient payment solution to mp3 users is one of the alternatives that can promote legal mp3 downloading. However, before the success of the payment solution can be determined, it is essential to understand whether it would be well-accepted by the users. This paper examines factors that influence the intention to use a mobile payment solution for mp3 downloading among university' students. Drawing from the Technology Acceptance Model, Theory of Planned Behaviour and previous literatures, five factors were hypothesized to influence the intention to use the payment solution, namely perceived usefulness, perceived ease of use, trust, perceived price level, and peer influence. Final year business students at a public university in the southern part of Malaysia were chosen as respondents for this study. Multiple regressions were employed to analyze the data. Two factors were found to have significant effect on the intention to use the payment solution, which were trust and peer influence. Practical implications were proposed and discussed.